Recycled ceramic tile composite for automobile applications, a comparative study with Nissan Jeep Cherokee brake pad - Agunsoye, Johnson Olumuyiwa; Bello, Sefiu Adekunle; Bamigbaiye, Adeola; Odunmosu, Kayode Ayodele; Akinboye, Isaac (Engineering and Applied Science Research, 2018)
A ceramic tile/steel slag-graphite-Arabic gum composite was developed using conventional casting techniques for brake pad applications. The chemical properties of the phases present in the matrix of the developed composite were examined using X-ray diffractometry. Spatial configuration of the phases was viewed using scanning electron microscopy. Wear and thermal properties of the developed composite were also investigated. Comparisons of the properties of the developed composite and Nissan Jeep Cherokee brake pads were made. The results showed a partial homogeneity of second phase particles within a ceramic matrix. The developed composite brake pad showed better friction properties than commercial grade brake pads for up to 200 s. At longer times, the opposite was observed. The developed composite brake displayed lower wear rates (1.3 x 10-8, 1.8 x 10-8, 2.92 x 10-8 and 3.0 x 10-8 mm3/Nm at 25, 30, 35 and 40 N, respectively) and better thermal stability than those (2.1 x 10-8, 4.8 x 10-8, 6.15 x 10-8 and 4.2 x 10-8 mm3/Nm) of Nissan Jeep Cherokee brake pad. This implies an optimum combination of good wear resistance, friction properties and thermal stability for up to 200 s. Since brake application while driving is a short and intermittent process (< 3 minutes), the developed composite could serve as a replacement for asbestos brake pads for automobiles.